2000
DOI: 10.1007/3-540-46439-5_23
|View full text |Cite
|
Sign up to set email alerts
|

Mining Classification Rules from Datasets with Large Number of Many-Valued Attributes

Abstract: Abstract. Decision tree induction algorithms scale well to large datasets for their univariate and divide-and-conquer approach. However, they may fail in discovering effective knowledge when the input dataset consists of a large number of uncorrelated many-valued attributes. In this paper we present an algorithm, Noah, that tackles this problem by applying a multivariate search. Performing a multivariate search leads to a much larger consumption of computation time and memory, this may be prohibitive for large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…In their simulation, the overall mean prediction rate of the logit was 72.7%, whereas the hit rate for SVM was 85.9%. Similarly, Giuffrida, Chu, and Hanssens (2000) reported that a multivariate decision tree induction algorithm outperformed a logit model in identifying the best customer targets for cross-selling purposes.…”
Section: Computer Science Modelsmentioning
confidence: 99%
“…In their simulation, the overall mean prediction rate of the logit was 72.7%, whereas the hit rate for SVM was 85.9%. Similarly, Giuffrida, Chu, and Hanssens (2000) reported that a multivariate decision tree induction algorithm outperformed a logit model in identifying the best customer targets for cross-selling purposes.…”
Section: Computer Science Modelsmentioning
confidence: 99%
“…We used all 45,222 tuples in the Adult dataset and 12,960 tuples in the Nursery dataset. We considered decision tree [26], Naive Bayes classifier [27], [28], and classification rules [29], [30] as knowledge models. We used the classification accuracy to measure the quality of decision trees and Naive Bayes classifiers, and the number of preserved classification rules to measure classification rules.…”
Section: Methodsmentioning
confidence: 99%
“…Algorithm application to forecasting and direct marketing has been discussed in management and computer science literature (Cooper & Giuffrida, 2000;Giuffrida, Chu, & Hanssens, 2000). The authors and their affiliates conducted extensive benchmark testing of the KDS/Noah algorithm in application to promotion forecasting and demonstrated its superiority to multiple commercially available data mining solutions including SAS EnterpriseMiner, SOMine, CN2, Ripper, Apriory, CBA, and others (Krycha, 1999).…”
Section: Promotion-event Forecasting System-promocastmentioning
confidence: 99%